APLIKASI ASAM HUMAT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) VARIETAS TALAM 1 - Sepmiarti, Intan; Dulbari, Dulbari; Buana, Arum Sekar; Priyadi, Priyadi (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2025)
The decrease in soil fertility due to over use of chemical fertilizers encourages the need to increase farmer awareness in utilizing more environmentally friendly nutrient sources. One alternative used in this study is humic acid in powder form. The study aims to determine the effect of humic acid on the growth and yield of peanut (Arachis hypogaea L.) variety Talam 1. The study was conducted from November 2023 to January 2024 at the Polinela Organic Farm, Lampung State Polytechnic. The parameters observed included plant height, number of branches, chlorophyll content, leaf width, and leaf length; as well as harvest parameters such as pod weight, number of empty pods, and filled pods. The study used a one-factor Randomized Complete Block Design (RCBD) with a comparative treatment of humic acid doses to reduce the use of inorganic NPK fertilizers. The results showed that the height of peanut plants of Talam 1 variety at the age of 1 WAP and 5 WAP did not differ significantly in various applications of humic acid in powder form. The use of humic acid has the potential to increase pod weight per plant in the P2 treatment by 30% from the control and 18.7% from the recommended NPK dose treatment. Humic acid in powder form can be an alternative as an environmentally friendly soil conditioner to support the growth and production of peanuts.